PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS III SD NEGERI 31 LUBUKLINGGAU - Swari, Dita Nurindah; Asep Sukenda Egok; Willy Lontoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the Cooperative Learning model of the Student Teams Achievement Division (STAD) type in Pancasila Education for third-grade students at SD Negeri 31 Lubuklinggau in the 2024/2025 academic year. The research method used was quantitative with a pre-experimental design, specifically the one-group pre-test-post-test model. Based on data analysis results, the average pre-test score of students was 41.42, with no students achieving the minimum mastery criteria. After the implementation of the STAD cooperative learning model, the average post-test score increased to 87.5, with 21 out of 24 students achieving mastery. Hypothesis testing using the Z-test showed that Z count > Ztable (4.22 > 1.64), indicating that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the application of the STAD-type cooperative learning model has a significant effect on improving the learning outcomes of Pancasila Education for third-grade students at SD Negeri 31 Lubuklinggau.